2014
DOI: 10.17532/jhsci.2014.165
|View full text |Cite
|
Sign up to set email alerts
|

Early extubation after congenital heart surgery

Abstract: Introduction: Despite recent advances in anesthesia, cardiopulmonary bypass and surgical techniques, children undergoing congenital heart surgery require postoperativemechanical ventilation� Early extubation was definedas ventilation shorter than 12 hours� Aim of this study is to identify factors associated with successful early extubation after pediatric cardiac surgery�

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In a five-year cohort study of infants post repair for transposition of great arteries, greater CPB and cross-clamp times and minimum temperatures less than or equal to 30.4 degrees centigrade were associated with a lesser likelihood of IE [13]. Another five-year study demonstrated an inverse relationship between age and CPB time and early extubation [14].…”
Section: Discussionmentioning
confidence: 99%
“…In a five-year cohort study of infants post repair for transposition of great arteries, greater CPB and cross-clamp times and minimum temperatures less than or equal to 30.4 degrees centigrade were associated with a lesser likelihood of IE [13]. Another five-year study demonstrated an inverse relationship between age and CPB time and early extubation [14].…”
Section: Discussionmentioning
confidence: 99%